2023
DOI: 10.1177/08445621221150297
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Predictors of Compassion Satisfaction, Burnout and Secondary Traumatic Stress in Registered Nurses in an Eastern Canadian Province: A Cross-Sectional Study

Abstract: Background The quality of Registered Nurses’ worklife is impacting nurses’ mental health, and the standard of care received by clients. Contributing factors to nurses’ stress are the trauma of continuous caring for those in great suffering, and adverse working conditions. Objectives i) to explore the prevalence of work-related stress in a provincial sample of Registered Nurses; ii) to compare the levels of compassion satisfaction, burnout and secondary traumatic stress reported by nurses in hospital, community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Evidence has demonstrated that overburdened work environments can increase nurses' vulnerability to compassion fatigue (Sinclair et al, 2017;Xie et al, 2021). Compassion fatigue represents a negative impact of nurses' work-related stress, and decreases care capacity (Maddigan et al, 2023;Stamm, 2010;Yesil & Polat, 2023). Peters (2018) defined compassion fatigue as "a preventable state of holistic exhaustion that manifests as a physical decline in energy and endurance, an emotional decline in empathetic ability and emotional exhaustion, and a spiritual decline as one feels hopeless or helpless to recover those results from chronic exposure to others' suffering, compassion, high stress exposure, and high occupational use of self in the absence of boundary setting and self-care measures" (p. 470).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence has demonstrated that overburdened work environments can increase nurses' vulnerability to compassion fatigue (Sinclair et al, 2017;Xie et al, 2021). Compassion fatigue represents a negative impact of nurses' work-related stress, and decreases care capacity (Maddigan et al, 2023;Stamm, 2010;Yesil & Polat, 2023). Peters (2018) defined compassion fatigue as "a preventable state of holistic exhaustion that manifests as a physical decline in energy and endurance, an emotional decline in empathetic ability and emotional exhaustion, and a spiritual decline as one feels hopeless or helpless to recover those results from chronic exposure to others' suffering, compassion, high stress exposure, and high occupational use of self in the absence of boundary setting and self-care measures" (p. 470).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The chronic physical, emotional and psychological toll of providing quality care in complex and high‐pressure environments can become a “cost of caring” for nurses. This is due, in part, to the profession's relational nature, which can not only promote nurses' compassionate connections with patients but also deplete their emotional resources due to the inherent stress of nursing practice (Maddigan et al., 2023 ; Zhang et al., 2018 ). Such an unrelenting and emotional work environment can lead to increased compassion fatigue and reduced compassion satisfaction, which contributes to a panoply of negative outcomes for nurses, patients and healthcare organizations (Al‐Marri et al., 2020 ; Yu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation